Thermal Behavior and Kinetics of Shenmu Coal Pyrolyzed under Hydrogen-Rich or Methane-Gas-Rich Atmosphere - Chong Zou; Xi Li; Mengmeng Ren; Weian Wang; Hao Wu (Energies, 2023)
The pyrolysis characteristics of Shenmu coal under an atmosphere containing H2 (40%) and another containing CH4 (40%) were studied via a thermogravimetric analysis, and the kinetic parameters of pyrolysis were calculated by using a distributed activation energy model (DAEM). The results showed that H2 promoted the cleavage of CH-like functional groups by providing reactive hydrogen groups to combine with CH groups and –OH groups in the coal. However, the H2 and CH4 atmosphere inhibits the cleavage of oxygen-containing functional groups such as carbonyl groups and C–O groups, and this is unfavorable to the production of CO2 and CO. The pyrolysis weight-loss rate of raw coal decreases with the increase of the heating rate, and the weight-loss curve shifts to the high-temperature region. At the same conversion rate and pyrolysis temperature, the activation energy of pyrolysis under the H2 and CH4 atmospheres is lower than that under the N2 atmosphere, and the activation energy does not conform to the Gaussian distribution. The activation energy of pyrolysis was distributed in a narrow range, in which the activation energy of the H2 and CH4 atmospheres was concentrated in the range of 175–215 kJ/mol and 225–230 kJ/mol, respectively, and the activation energy of the H2 atmosphere was lower than that of the CH4 atmosphere under the same conversion rate.